PENDIDIKAN KORUPSI PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG DI INDONESIA(Sanksi Pidana Hukum Islam dan UU No. 20 Tahun 2001) - Ratno, Dedi (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2026)
This study was conducted to determine the thoughts of the Imams of the Madzhab on corruption and the basis of their respective thoughts. The research method used in this study is normative juridical research and can be concluded: 1. Corruption in the thoughts of the Imams of the Madzhab is an act that violates sharia. Islamic law aims to realize the benefit for humanity with what is called maqashidussy sharia. Perspective of the broader context of Islamic teachings, the practice of corruption is an act that is contrary to the principles of justice, accountability, and responsibility. Corruption can cause various distortions to the life of the State and society that can be categorized as acts of damage on earth (fasad). 2. The basic thinking of the Imam of the madzhab regarding punishment for perpetrators of corruption is to place corruption in the category of takzir crimes. Takzir is a legal sanction imposed on a person who commits a crime or crime that violates both the rights of Allah SWT and human rights. These violations are not expressly specified in the texts of the Quran and Hadith. Because they are not expressly specified, takzir falls under the competence of judges or local authorities. Takzir legal sanctions can include imprisonment, fines, inclusion on the list of disgraced persons, dismissal, and even the death penalty